ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN MASALAH PERMUTASI DAN KOMBINASI - Matitaputty, Christi; Mataheru, Wilmintjie; Talib, Taufan (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2022)
Permutations and combinations are one of the materials in discrete mathematics courses that have many benefits in everyday life and are closely related to the context of real life. However, students need to improve in solving permutation and combination problems. This study aims to describe the errors made by students in solving permutation and combination problems. The research subjects comprised 25 first-semester students of the 2021/2022 academic year of the Mathematics Education Study Program, FKIP Unpatti. The research method used is descriptive qualitative. The research instrument consisted of 6 test questions related to permutations and combinations. The results showed that most students made mistakes because they needed help understanding the statement (58%). In addition, students also made mistakes in remembering value parameters (13%), paying attention to order (10%), recognizing objects (8%), using formulas (7%), and errors in performing arithmetic operations (4%). The implications of this research are expected to be able to contribute to lecture activities in the first year